An analysis of One Health timeliness metrics across multisectoral public health emergencies in Uganda - Jane K. Fieldhouse; Lydia Nakiire; Joshua Kayiwa; Ali Mirzazadeh; Claire D. Brindis; Ashley Mitchell; Jaime Sepulveda; Issa Makumbi; Alex Riolexus Ario; Elizabeth Fair; Sarah Gallalee; Herbert Isabirye; et al. (Communications Medicine)
Abstract Background Timeliness metrics offer countries a framework by which to assess and optimize speed in outbreak detection and response times. This study analyses the One Health timeliness metrics for multisectoral public health emergencies in Uganda to identify and explore factors influencing outbreak performance. Methods We compiled a database of outbreak events in Uganda occurring between 2018-2022 and involving the human, animal, plant, and environmental sectors. Outbreak milestone dates were extracted from reports to calculate timeliness metrics, which were analyzed using proportional hazards regression models. Concurrently, we conducted Key Informant Interviews to explore factors affecting detection and response timeliness. Results Integrated analyses of timeliness metrics from 81 outbreaks and expert interviews reveal that the greatest predictors of improved timeliness are frequent past experience with similar disease outbreaks and whether an outbreak is a viral hemorrhagic fever due to heightened perceived threat and pre-existing preparedness measures. Other factors, including diagnostic and laboratory considerations and contextual influences, such as One Health collaborations, are also described as relevant to timeliness. Conclusions To complement positive timeliness trends in Uganda, disease-agnostic investments in outbreak preparedness and response efforts will facilitate the ability of health systems to rapidly detect and respond to all outbreaks, irrespective of the pathogen.